PERBAIKAN TANAH LANAU UNTUK BAHAN JALAN MENGGUNAKAN LIMBAH BATA - - Endaryanta (Universitas Negeri Yogyakarta, 2010)
ABSTRACTThe earthquake in Bantul, Yogyakarta at Mei 27, 2006 appeared a lot ofproblems for peoples. Besides psychological and physical excesses,, a great deal ofthe rubbish material accumulated as the result of building destruction. This paper triesto implement the brick rubbish material for improving the soil street strength atvillages. This experiment research that was done by CBR-test at pure soil as well as atsoil with grain brick mixture is aimed to explain the appropriate grain brick compositionmust be mixed into soil in order to get a maximum strength of soil. The results of theresearch are: 1. adding grain brick into soil could increase the strength of soil bearingparallel with increasing the CBR-value.2. the fine grain brick significantly increase thestrength of soil mix. 3. the CBR-value of soil mixed with grain brick is reached at36%.Keywords : brick, rubbish, CBR, soil bearing, soil strength.